Identification Of Liquefaction-Potential Zones Using The Gravity Method In Lolu Village, Central Sulawesi - Meschac Timothee Silalahi; Darharta Dahrin; Dadi Abdurrahman; Adrin Tohari (Postgraduate, University of Mataram, 2023)
A seismic event of magnitude 7.5 struck the Palu region in Central Sulawesi on September 28, 2018, precipitating a subsequent calamity in the form of a tsunami measuring 4-7 meters in height. This catastrophe was further compounded by the occurrence of liquefaction, leading to extensive devastation and a significant loss of life. In order to identify areas susceptible to liquefaction, it is anticipated that the employment of the gravity method, renowned for its capacity to discern density fluctuations associated with the mass of voluminous materials over a considerable detection range, will prove instrumental. The investigation of parameters and the characterization of liquefaction phenomena in regions previously afflicted by liquefaction disasters can be instrumental in devising strategies for mapping zones that are predisposed to such occurrences. The present study seeks to employ geophysical methods, specifically the gravity method, to delineate zones with the potential for liquefaction within the Lolu Village at Palu City, Central Sulawesi. Through the application of techniques designed to isolate regional and residual anomalies, it is envisaged that a clearer understanding of anomalies situated in shallower regions can be attained, with a specific focus on residential areas. Notably, due to liquefaction, approximately half of the residential areas have shifted a considerable distance of around 132 meters from their original positions. To facilitate the interpretation of subsurface layers, two-dimensional cross-sections are modeled to intersect the displaced and stationary areas. The residual map reveals discernible variations in anomaly values, with lower values observed in the areas that experienced liquefaction-induced movement. Subsurface modeling further demonstrates the presence of three distinct rock layers, namely a sandy layer, a gravel layer, and a rock layer. Additionally, the modeling depicts the formation of canals composed of hard rock, exhibiting varying thicknesses within the surface layer as a consequence of the liquefaction event in 2018. The existence of these canals serves as an indicator that when the sandy layer becomes saturated with water, it will flow along the topographical gradient, following the path of the subterranean canals that have formed.